Necessary and sufficient conditions for global-in-time existence of solutions of ordinary, stochastic, and parabolic differential equations (Abstract and Applied Analysis)
We derive necessary and sufficient conditions for global-in-time existence of solutions of ordinary differential, stochastic differential, and parabolic equations. The conditions are formulated in terms of complete Riemannian metrics on extended phase spaces (conditions with two-sided estimates) or in terms of derivatives of proper functions on extended phase spaces (conditions with one-sided estimates).